A Primary Care Perspective on Prevailing Assumptions about Persistent Medically Unexplained Physical Symptoms - Stanley, Ian M.; Peters, Sarah; Salmon, Peter (International journal of psychiatry in medicine, 2002)
Objective: To re-examine the widespread assumption that medically unexplained physical symptoms represent discrete syndromes resulting from somatization of mental illness. Method: Primary care patients (N = 223) with medically unexplained symptoms of at least one year's duration were recruited to a study of exercise therapy. Data gathered from patients, from their general practitioners, and from medical records were used to examine relationships between self-defined disability, symptoms, mental state, and use of health care. Results: Levels of disability and health care use were both raised, but were only weakly correlated. While most patients were depressed and/or anxious, a minority (14 percent) were neither. Although mental state correlated with disability, health care use was unrelated to either. Among a wide range of recorded symptoms, few correlations were found to support the existence of discrete syndromes. Analysis of agreement between patients and their doctors in assigning symptoms to broadly defined “syndromes” appears to reflect collaboration that is largely expedient. Conclusions: In this sample of primary care patients with persistent unexplained physical symptoms, we found little evidence of discrete somatic syndromes. The level of health care use is no indication of mental state or level of disability, and the findings are equally consistent with depression or anxiety being secondary to disability and its consequences as with them being primary. The observed collaboration between patients and their doctors carries the risk of shaping, reinforcing, and legitimizing dubious syndromes.